2020
DOI: 10.1016/j.jagp.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Early Psychological Correlates Associated With COVID-19 in A Spanish Older Adult Sample

Abstract: HIGHLIGHTS This study examined the early psychological correlates associated with the COVID-19 pandemic and lockdown in an older adult sample. Regardless of mental status, depressive and avoidant style were the most prevalent in this older adult sample. Interventions need to be tailored to alleviate dysfunctional coping strategies and their progression to mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
4
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 31 publications
2
44
4
4
Order By: Relevance
“…Older adults reported a presence or worsening of psychological symptoms, and greater loneliness because of pandemic-related social isolation [ 33 , 38 , 47 , 49 , 51 , 52 , 56 , 57 , 62 , 63 , 77 , 78 , 84 , 89 , 90 , 99 , 105 , 114 , 117 , 128 , 135 , 139 , 140 , 148 , 156 , 160 ]. Compared to younger age, older age (ie, ≥60 years) was, however, associated with fewer psychological symptoms [ 39 , 44 , 50 , 54 , 57 , 59 , 64 - 67 , 74 , 77 , 89 , 95 , 97 , 98 , 101 , 107 , 109 , 111 , 114 , 116 , 120 , 121 , 124 , 125 , 127 , 136 , 138 , 147 , 151 , 153 , 157 , 158 , 161 , 162 , 165 ], lower loneliness [ 92 , 95 , …”
Section: Resultsmentioning
confidence: 99%
“…Older adults reported a presence or worsening of psychological symptoms, and greater loneliness because of pandemic-related social isolation [ 33 , 38 , 47 , 49 , 51 , 52 , 56 , 57 , 62 , 63 , 77 , 78 , 84 , 89 , 90 , 99 , 105 , 114 , 117 , 128 , 135 , 139 , 140 , 148 , 156 , 160 ]. Compared to younger age, older age (ie, ≥60 years) was, however, associated with fewer psychological symptoms [ 39 , 44 , 50 , 54 , 57 , 59 , 64 - 67 , 74 , 77 , 89 , 95 , 97 , 98 , 101 , 107 , 109 , 111 , 114 , 116 , 120 , 121 , 124 , 125 , 127 , 136 , 138 , 147 , 151 , 153 , 157 , 158 , 161 , 162 , 165 ], lower loneliness [ 92 , 95 , …”
Section: Resultsmentioning
confidence: 99%
“…American Psychiatric Association, 2013 , Bobes-Bascará n et al, 2020 , World Health Organization, 2020a , World Health Organization, 2020b .…”
Section: Uncited Referencementioning
confidence: 99%
“…All seniors showed anxiety and depression issues in China, and results were worse for females [35]. A Spanish study reported that up to 25.6% of a sample of adults with a mean age of 65 had symptoms of depression and 32.1% symptoms of avoidant coping style, and that having a current or past history of mental disorders highly influenced this, while the main protective factor was the ability to enjoy free time [36]. However, we found that younger people coped worse than older people with the mental burden due to the Covid-19 pandemic and the measures dictated to combat it.…”
Section: Discussionmentioning
confidence: 99%